Perilaku Reaksi Harga Dan Volume Perdagangan Saham terhadap Pengumuman Dividen - BANDI BANDI; JOGIYANTO HARTONO (The Indonesian Journal of Accounting Research, 2013)
Many of researches on price and volume reaction associated with the earnings announcement have been conducted. Bamber and Cheon (1995) acknowledge that there is a positive relation between the average of magnitudes of price and of volume reaction. Nearly a quarter of the quarterly earning announcements generate price and volume reaction of different relative magnitudes. Surprisingly, there is little empirical evidence of such reaction regarding the dividend announcements. This research investigates the volume and price reactions associated with the dividend announcements.The result of this study shows a dependence between price and volume reaction. Additionally, price and trading volume is positively related.Although there is a relation between price and volume reaction around dividend announcements, the reactions are very relatively different in magnitudes. The relative magnitudes of price and volume reactions are extremely different for 32,88 percent of these sample dividend announcements, relatively similar reactions for 30,87 percent, and the remaining 36,24 percent shows relatively indeterminate reactions.